Tolerance signaling molecules and pregnancy: IDO, galectins, and the renaissance of regulatory T cells - Terness, Peter (2007)
Is the concept of maternal tolerance preventing rejection of the semi-allogeneic 'fetal allograft' still valid?. Compilation of expert reviews of literature and recent advances in research on indoleamine-2,3 dioxygenase (IDO), regulatory T cells and galectin-1. A role for IDO in pregnancy success remains speculative, but solid data exist to support a role for Treg cells, and for galectin-1 in induction and action of Treg cells. Just as several signals may need to be simultaneously present to induce Th1 cytokine-triggered abortions, more than 1 signal may need to be simultaneously present to prevent rejection and ensure success. Both complement and coagulation pathways appear necessary for embryo execution.